Review on Rural Energy Access Policies - Cabello-Vargas, Enrique; Escobedo-Izquierdo, Azucena; Morales-Acevedo, Arturo (International Journal of Energy Economics and Policy, 2021)
Rural energy in all their dimensions, not only access, but also sources, supply, consumption, program management, project maintenance, control and evaluation has been a neglected area in national energy planning in developing countries. As a result, nearly two billion people all around the world lack access to commercial energy, particularly to electricity and clean cooking appliances. Poor people still depend on traditional sources of energy that are used inefficiently. The unplanned exploitation of local biomass resources, mainly for basic needs such as cooking, generates serious environmental problems. In this sense, women face hardship in the collection of biomass and exposure to smoke that adversely affect their health. Therefore, this study aims to explore rural energy policies through a systematic literature review about rural energy access as a problem to be solved by means of an adequate rural energy policy. The study tries to raise the general settings of rural energy access, their challenges, barriers, and alternatives for solution, especially through the consideration of rural energy policy as an alternative to achieve a sustainable solution for rural poverty. Besides, by organizing and collecting concepts, this review contributes to a better understanding of these topics and their general issues, particularly in Latin America. Considering the general context as an initial condition, and the universal energy access as the perfect condition, rural energy policy becomes the central strategy to ensure universal energy access in all rural areas, trying to transit from an initial to a perfect condition. Keywords: Rural energy policy, Rural energy access, Rural energy poverty, Rural electrification, Clean cooking alternatives. JEL Classifications: Q40, Q43, Q48, Q49, R10, R58 DOI: https://doi.org/10.32479/ijeep.11268